2022
DOI: 10.3390/pr10122588
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Supercritical Fluid Decellularized Porcine Acellular Dermal Matrix in the Post-Repair of Full-Thickness Abdominal Wall Defects in the Rabbit Hernia Model

Abstract: Damage to abdominal wall integrity occurs in accidents, infection and herniation. Repairing the hernia remains to be one of the most recurrent common surgical techniques. Supercritical carbon dioxide (SCCO2) was used to decellularize porcine skin to manufacture acellular dermal matrix (ADM) for the reparation of full-thickness abdominal wall defects and hernia. The ADM produced by SCCO2 is chemically equivalent and biocompatible with human skin. The ADM was characterized by hematoxylin and eosin (H&E) stai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…In addition to this evidence for altered mechanical properties, stiffer abdominal wall scaffolds have been observed in other studies conducted with similar preparation methods. Specifically, Sanchez et al [36], Buell et al [37], and Chiu et al [38] demonstrated decellularized abdominal wall constructs with similar biomechanical properties as those presented herein. The immunogenicity of decellularized scaffolds constitutes another important parameter for them to serve as potential biological grafts.…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…In addition to this evidence for altered mechanical properties, stiffer abdominal wall scaffolds have been observed in other studies conducted with similar preparation methods. Specifically, Sanchez et al [36], Buell et al [37], and Chiu et al [38] demonstrated decellularized abdominal wall constructs with similar biomechanical properties as those presented herein. The immunogenicity of decellularized scaffolds constitutes another important parameter for them to serve as potential biological grafts.…”
Section: Discussionsupporting
confidence: 65%
“…The preservation of collagen type I in decellularized samples is of significant importance, being one of the major proteins of the ECM structure, thus contributing to a great number of processes, such as hemostasis performance and regulation of the wound-healing process in the injured area [ 41 ]. In addition to its function in tissue healing, collagen type I plays a significant role in the recruitment and attachment of specific cellular populations to the wounded region through binding to arginine–glycine–aspartic acid (RGD) binding motifs [ 34 , 35 , 37 , 38 , 42 , 43 , 44 , 45 , 46 , 47 ]. Indeed, various cellular populations, such as fibroblasts, pericytes, and mesenchymal stromal cells, can bind to collagen fibers through the interaction of α1β1, α2β1, and ανβ1 with the RGD binding motifs of well-aligned collagen fibers, thus further promoting wound healing and tissue regeneration [ 34 , 35 , 37 , 38 , 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations